Integration Model Productive Business as Embryo Oyster Mushroom in Village Klakah District Lumajang - Ainun Jariah; Fauzan Muttaqin; Nawangsih Nawangsih (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Research Purposes : to realize Small and Medium Industries (IKM) that are globally empowered in solving social problems through product downstreaming. Design/methodology/approach: The research method is descriptive qualitative, using direct observations and interviews and documentation. Findings: The Oyster Mushroom Farmer Group has applied the management function (organizing), business administration starts to be organized by implementing the economic entity principle, has applied a more effective online marketing strategy, graphic design for the packaging of all product innovations has followed the proper provisions, especially innovation for packaging. oyster mushroom products Limitations/Implications Research: the data sources only came from the head, farmers, and processors of the "Manut" Oyster Mushroom Farmers Group. Practical Implications: to transfer of knowledge from universities to the participants of the "Manut" Oyster Mushroom Farmers Group, especially business management, business administration, effective online marketing strategies, graphic design, and product innovation made from oyster mushrooms. Originality/Value: Integration Model Productive Business as Embryo Oyster Mushroom in Village Klakah District Lumajang Type of Paper: research paper